Pengaruh citra merek, iklan, kualitas yang dirasa terhadap keputusan pembelian sim card Telkomsel di Surabaya - Indra Nandaputra Lasaib; Emma Yulianti (Journal of Business & Banking, 2019)
The purpose of this study to determine whether the image of the brand, advertising, and perceived quality has a significant influence either simultaneously or partially on purchasing decisions Telkomsel SIM card in Surabaya. This study uses the entire population of Surabaya people who use Telkomsel as their mobile telephone operator. In this study, judgement sampling technique to adapted the characteristics specified by the researcher. The sample in this study using 80 respondents people of Surabaya who use Telkomsel as their mobile telephone operator. The data used are primary data and their were collected through a survey using a questionnaire. Data were analyzed using descriptive analysis, classic assumption test and multiple linear regression analysis using SPSS 20. Based on the calculations and the results are known hypothesis that the image of the brand, advertising, and perceived quality has a significant influence either simultaneously or partially on purchasing decisions Telkomsel SIM card in Surabaya.